Politik Hukum Penerapan Diversi Pada Sistem Peradilan Pidana Anak Untuk Mewujudkan Keadilan Restoratif - Dhoni Martien (Universitas Jayabaya, 2017)
Restorative Justice and Diversity which are intended to avoid and keep children away from the judicial process so as to avoid stigmatization of children in conflict with the law and are expected to return children to the social environment naturally. The research method used in this study is normative juridical using three approaches, namely the statutory approach, conceptual approach, and historical approach. The data source used is secondary data, which consists of primary legal materials, secondary legal materials and tertiary legal materials. As a knife analysis, researchers use the Legal System Theory as Grand Theory, Authority Theory as Middle Range Theory, Criminal Theory as Applied Theory. The results of this study found that The application of diversion in the juvenile justice system in Indonesia, in realizing restorative justice in the court has been carried out, based on Government Regulation Number 65 of 2015 concerning Government Regulation Guidelines for the Implementation of Diversity and Handling of Children who are not yet 12 (Twelve) Years Old. Political Law that must be taken by the Government is amending Government Regulation Number 65 of 2015 concerning guidelines for implementing diversion and handling children who are not yet 12 years old, by adding provisions governing Special Investigators, Special Public Prosecutors and Special Judges, who handle diversion in the justice system child.